μ-Opioid Receptor Desensitization in Mature Rat Neurons: Lack of Interaction between DAMGO and Morphine - Bailey, Christopher P. (J Neurosci, 2003)
μ-Opioid receptors (MORs) exhibit rapid desensitization and internalization during exposure to various opioid agonists. In some studies, however, morphine has been observed to produce little MOR desensitization or internalization. We examined desensitization in mature rat locus ceruleus (LC) neurons and confirmed that morphine is a very poor desensitizing agent, whereas [d-Ala(2),N-MePhe(4),Gly-ol(5)]enkephalin (DAMGO), a high-efficacy agonist, and methadone, an agonist we observed to be of equivalent efficacy to morphine, produced profound rapid desensitization. Similarly, by measuring plasma membrane receptor levels in HEK293 cells stably expressing T7-epitope-tagged rat MOR1 at near physiological levels (HEK293-MOR1 cells), DAMGO and methadone but not morphine caused rapid MOR internalization. It has been reported that a low concentration of DAMGO, coapplied with morphine, caused morphine to induce MOR internalization. We examined whether this interaction occurred in mature mammalian neurons at the level of receptor desensitization. Coapplication of low concentrations of DAMGO did not increase morphine-induced desensitization in LC neurons but caused a lesser degree of desensitization than DAMGO alone. We also failed to observe an enhancement by DAMGO of morphine-induced desensitization in the electrically stimulated guinea pig ileum myenteric plexus-longitudinal muscle preparation. In HEK293-MOR1 cells, low concentrations of DAMGO did not convert morphine into a receptor-internalizing agent. The data presented here fail to support the theory that low concentrations of DAMGO can increase morphine-induced MOR desensitization or internalization.